Vaping in Pregnancy: A Systematic Review. Issue 9 (4th February 2021) - Calder, Robert; Gant, Eleanor; Bauld, Linda; McNeill, Ann; Robson, Debbie; Brose, Leonie S
Abstract: Introduction: Smoking in pregnancy increases the risk of negative health outcomes. Vaping can be effective for smoking cessation in nonpregnant populations. We conducted a systematic review of vaping in pregnancy, covering prevalence, patterns of use, reasons for use, smoking cessation, and health effects. Methods: Five academic databases were searched on 17 February 2020. Studies reporting prevalence, patterns, reasons, cessation, or health effects of vaping in pregnancy were included; animal and in vitro studies were excluded. A narrative review was used, with risk of bias assessed using Hoy and colleague's tool, the Newcastle–Ottawa scale, and the Consolidated Criteria for reporting Qualitative Research. Results: Twenty-three studies were identified: 11 survey, 7 qualitative, 3 cohort, and 2 secondary analyses of randomized clinical trials. Prevalence of vaping in pregnancy (four studies) was between 1.2% and 7.0% overall, and <1% among nonsmokers. Twelve studies reported patterns of use, but findings were inconsistent. Twelve of 14 studies asking why pregnant women vaped reported that most vaped to reduce or quit smoking. Mixed findings were reported from six studies on smoking cessation. Of three studies with health-related outcomes, two were underpowered and one reported similar birthweights for babies born to nonsmokers and women who vaped, with both higher ( p < .0001) than the birthweight of babies born to smokers. Conclusions: There were insufficient data to draw conclusions about prevalence, patterns, and effects of vaping in pregnancy on smoking cessation. The limited literature suggests that vaping in pregnancy has little or no effect on birthweight. Implications: Smoking causes many negative health outcomes for pregnant women and to babies born to people who smoke. There remains a paucity of research on the effects of vaping in pregnancy. There is, however, the potential for vaping products to reduce the negative health outcomes associated with smoking. More research is needed to develop an evidence base in this area.